LEVETIRACETAM IS INDEPENDENTLY ASSOCIATED WITH FATIGUE IN ADULT GLIOMA OUTPATIENTS. Issue 11 (14th October 2015) - Zienius, Karolis; Rooney, Alasdair; Grant, Robert
Abstract : Aims: To identify the frequency and severity of fatigue in adults with cerebral glioma, and its association with anti-epileptic drugs (AED). Methods: Cross-sectional study. Stable glioma patients attending Edinburgh Neuro-Oncology clinic completed a fatigue Visual Analogue Scale (range 0-100mm, "high" >=60 mm). AED type and dose were recorded. Results: One hundred and sixty six patients were enrolled (61% males; mean age 49 yrs; 70% high-grade glioma). Among all patients, 43% reported high fatigue (95% CI 35–50%). Sixty eight percent were taking AEDs (58% of which were non enzyme inducing). Levetiracetam (LEV) was the most common AED. LEV monotherapy correlated with higher fatigue levels (mean=57 mm, SD 5.2, 95% CI 46–67 mm), compared with other AEDs (mean=43 mm, SD 3.9, 95% CI 35–50 mm, ANCOVA p=0.04). Patients taking LEV had poorer Karnofsky Performance Scores (KPS, Mann–Whitney p=0.03). The effect of LEV on fatigue was independent of KPS (LR p<0.0001, R2= 27.7, OR 2.7 [1.1–6.2]). Conclusions: Glioma patients on levetiracetam therapy are more fatigued than patients on other or no anti-epileptic therapy. Changes to AED medications may benefit patients with troublesome fatigue.